A general strategy for direct, enzyme-catalyzed conjugation of functional compounds to DNA. Issue 11 (13th March 2018) - Deen, Jochem; Wang, Su; Van Snick, Sven; Leen, Volker; Janssen, Kris; Hofkens, Johan; Neely, Robert K
Abstract: The methyltransferase enzymes can be applied to deliver a range of modifications to pre-determined sites on large DNA molecules with exceptional specificity and efficiency. To date, however, a limited number of modifications have been delivered in this way because of the complex chemical synthesis that is needed to produce a cofactor analogue carrying a specific function, such as a fluorophore. Here, we describe a method for the direct transfer of a series of functional compounds (seven fluorescent dyes, biotin and polyethylene glycol) to the DNA duplex. Our approach uses a functional cofactor analogue, whose final preparative step is performed alongiside the DNA modification reaction in a single pot, with no purification needed. We show that fluorophore conjugation efficiency in these mixtures is significantly improved compared to two-step labeling approaches. Our experiments highlight the remarkable malleability and selectivity of the methyltransferases tested. Additional analysis using high resolution localization of the fluorophore distribution indicates that target sites for the methyltransferase are predominantly labeled on a single strand of their palindromic site and that a small and randomly-distributed probability of off-site labeling exists.